2019
DOI: 10.1037/aca0000176
|View full text |Cite
|
Sign up to set email alerts
|

The expression of schizotypy in the daily lives of artists.

Abstract: A considerable amount of research suggests that positive schizotypy (cognitive and perceptual aberrations, such as pseudo-hallucinations) is associated with creativity in the arts.In order to better understand how positive schizotypy might be expressed in the creative process, the experience sampling method was used to explore the experiential correlates of schizotypy in a sample of artists. Artists (N = 41) were sampled over a week-long period, answering questions at random intervals that related to mood, cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 79 publications
(176 reference statements)
2
31
0
Order By: Relevance
“… Nelson & Rawlings (2010) found elevated levels of positive schizotypy in a sample of 100 hundred artists, and positive schizotypy was a robust predictor of immersion in creating art and the associated sense of anxiety, and also of power and pleasure experienced during performing creative activities. A recent experience sampling study also found elevated positive schizotypy among artists ( Holt, in press ), and in this sample, positive schizotypy predicted experiences of flow, vivid visual imagery, introspection, and absorption in daily life. Importantly, positive schizotypy was not only correlated with art-making and inspiration, but it was also associated with increased positive affect and self-esteem during and after creating artwork.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“… Nelson & Rawlings (2010) found elevated levels of positive schizotypy in a sample of 100 hundred artists, and positive schizotypy was a robust predictor of immersion in creating art and the associated sense of anxiety, and also of power and pleasure experienced during performing creative activities. A recent experience sampling study also found elevated positive schizotypy among artists ( Holt, in press ), and in this sample, positive schizotypy predicted experiences of flow, vivid visual imagery, introspection, and absorption in daily life. Importantly, positive schizotypy was not only correlated with art-making and inspiration, but it was also associated with increased positive affect and self-esteem during and after creating artwork.…”
Section: Discussionsupporting
confidence: 64%
“…Further research, however, should corroborate and extend these findings by including the measurement of objective sleep parameters. Moreover, future studies should characterise the dynamics of causality between sleep disturbances and schizotypy ( Barton et al, 2018 ) and also between creative accomplishments and mental health ( Amabile et al, 2005 ; Holt, in press ).…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] Interestingly, some studies have showed a correlation between positive schizotypy and health and\or well-being, possibly indicating a trait of benign schizotypy. 10,11,35 Of note in Figure 2 is the difference between factor loadings and threshold parameters in each item's box. Figure 2) is not very high, which indicates that this is not a very severe item, meaning it is not so unlikely that a person will endorse this question.…”
Section: Discussionmentioning
confidence: 99%
“… 32 - 34 Interestingly, some studies have showed a correlation between positive schizotypy and health and\or well-being, possibly indicating a trait of benign schizotypy. 10 , 11 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…3 Another reason for the interest of artists in depicting subjective experiences was that some of them had unusual experiences that were not being recognized in polite company then (or, to an ex-DEPICTING THE ETHEREAL, PART I: VISUAL ART AND PSI tent, now, see Cardeña et al, 2017). This is expectable since artists tend to experience "thinner" mental boundaries between them and the "outside" world than average (Hartmann et al, 2001), blurring distinctions between "inner" and "outer" experiences, and have uncommon perceptual experiences and beliefs (Holt, 2019). That the latter are not only "subjective" is suggested by controlled psi experiments, in which artists tend to perform significantly better than chance (e.g., having a 50% hit rate when 25% would be expected by chance, Schlitz & Honorton, 1992) and better than individuals who are not artists or do not follow mental disciplines such as meditation (Baptista et al, 2015).…”
mentioning
confidence: 99%